MAKNA DAN PENGHAYATAN PROFESI PUSTAKAWAN - Heriyanto, Heriyanto; Yusup, Pawit M; Rusmana, Agus (Jurnal Kajian Informasi dan Perpustakaan, 2013)
This study aims to examine the meaning and appreciation of the librarians in college to his profession as a librarian. This study used a qualitative approach with phenomenological method in the constructivist paradigm-interpretive. The study involved nine librarians from several college libraries as key informants. This study found there were 8 meaning of librarian, which librarians as a helper, a librarian as an educator, a librarian as discussion partners, librarians as consultants, librarians as counselors, librarians as information managers, librarians as facilitators of information, and librarians as a promising profession. While the form of appreciation for the profession of librarians can be expressed in the decision to keep living as a librarian although there are many other offers that offer more in terms of welfare, willingness to give time and attention even if outside of working hours, proud to mention his profession as a librarian, always ready to provide services prime, and always trying to innovate in doing the job.Penelitian ini bertujuan untuk meneliti makna dan penghayatan dari para pustakawan di perguruan tinggi terhadap profesinya sebagai pustakawan. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologis dalam paradigma konstruktivis-interpretif. Penelitian ini melibatkan 9 orang pustakawan dari beberapa perpustakaan perguruan tinggi sebagai key informan. Penelitian ini menemukan ada 8 makna dari profesi pustakawan, yaitu pustakawan sebagai penolong, pustakawan sebagai pendidik, pustakawan sebagai teman diskusi, pustakawan sebagai konsultan, pustakawan sebagai pembimbing, pustakawan sebagai manajer informasi, pustakawan sebagai fasilitator informasi, dan pustakawan sebagai profesi yang menjanjikan. Sedangkan bentuk penghayatan terhadap profesi pustakawan dapat terekspresi dalam keputusan untuk tetap berprofesi sebagai pustakawan walaupun ada banyak tawaran lain yang menawarkan lebih banyak dalam hal kesejahteraan, kesediaan untuk memberikan waktu dan perhatian walaupun di luar jam kerja, bangga menyebutkan profesinya sebagai pustakawan, selalu siap memberikan pelayanan prima, dan selalu berusaha untuk melakukan inovasi dalam melakukan pekerjaan.